كفاية الإجراءات الرقابية في الحزم البرمجية المحاسبية الجاهزة - حالة تطبيقية – (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث كيفية تحقيق تطويرللرقابة الداخلية في النظم المؤتمتة من خلال تحليل نظامين محاسبيين. وقد تطرّق البحث لتبيان مدى الحاجة لوجود معايير وأسس للرقابة في المنشآت التي لديها نظم معالجة مؤتمتة، وقد تناول هذا البحث أيضاً أساليب الرقابة الداخلية والرقابة التطبيقية والعامة لكل من النظم اليدوية والنظم المؤتمتة والمشاكل التي يمكن حدوثها ضمن بيئة التحكم بالنظم المحاسبية المؤتمتة، كما أكد البحث على ضرورة وضع معايير وأسس تحكم عملية الرقابة في النظم المؤتمتة، وبناء على هذه الدراسة فقد تم تقديم مجموعة من التوصيات والنتائج تعتمد بشكل أساسي على المطالبة بإجراء تحليل نظام في أي شركة قبل وضع قاعدة بيانات ونظام الأتمتة المحاسبية لها مع مراعاة مقوّمات جيدة للرقابة الداخلية ووسائل التحكم ورفع أدائها وتقديم البيانات المحاسبية اللازمة للإدارة مبنية على معلومات موثوقة بما ينعكس على عملية إتخاذ القرار المثالي في الوقت المناسب. This research deals with the way to realize the development of the interial supervision in the automated systems through the analysis of two accountancy systems. The research intended to explain the extent of need of the presence of norms and bases of supervision in the establishments that have automatic processing systems. It, also, delt with interior supervisory, applied, and general supervisory to each of the manual and automated systems and problems that may arise inside of the environment of control of automated accountancy systems. The research, as well, emphasized the necessity of putting norms and bases of control of the operation of supervision in automated systems. This study had presented a group of recommendations and results depending basically upon the demand to execute system analysis in any company before putting data basis and automated accountancy system taking into consideration good constituents of interior supervisory and means of control. This is to raise its performance and to introduce necessary accountancy data to the administration based on reliable informations which help taking the proper decision in the proper time.